Application of RNS in refractory epilepsy: Targeting insula. Issue 3 (4th July 2017) - Chen, Hai; Dugan, Patricia; Chong, Derek J.; Liu, Anli; Doyle, Werner; Friedman, Daniel
Summary: Although responsive neurostimulation (RNS) is approved for treatment of resistant focal epilepsy in adults, little is known about response to treatment of specific cortical targets. We describe the experience of RNS targeting the insular lobe. We identified patients who had RNS implantation with at least one electrode within the insula between April 2014 and October 2015. We performed a retrospective review of preoperative clinical features, imaging, electrocardiogram (EEG), intraoperative electrocorticography (ECoG), and postoperative seizure outcome. Eight patients with at least 6 months of postimplant follow‐up were identified. Ictal localization was inconclusive with MRI or scalp EEG findings. Intracranial EEG monitoring or intraoperative ECoG demonstrated clear ictal onsets and/or frequent interictal discharges in the insula. Four patients demonstrated overall 50–75% reduction in seizure frequency. Two patients did not show appreciable seizure improvement. One patient has experienced a 75% reduction of seizure frequency, and another is nearly seizure free postoperatively. There were no reported direct complications of insular RNS electrode placement or stimulation, though two patients had postoperative complications thought to be related to craniotomy (hydrocephalus and late infection). Our study suggests that insular RNS electrode placement in selected patients is relatively safe and that RNS treatment may benefit selected patients with insular epilepsy.